Summation of Precordial R Wave Amplitudes, a Clinical Parameter for Detecting Early TTR Amyloidosis Cardiac Involvement - Yoshitaka Isotani; Eisuke Amiya; Junichi Ishida; Issei Komuro (Journal of Cardiovascular Development and Disease, 2022)
There have been several reports on the identification of the stage of transthyretin amyloid cardiomyopathy (ATTR-CM); however, a staging system for ATTR-CM has not yet been established. An 83-year-old woman was referred to our department about ten years ago. Recently, she was diagnosed with ATTR-CM. The electrocardiogram showed characteristic changes that take place over the duration of ATTR-CM progression. Among these, the precordial R amplitudes abruptly decreased before the development of increased ventricular thickness. This case suggested that the decrease in the precordial R wave amplitudes may represent a new diagnostic clue reflecting early myocardial damage due to ATTR-CM.